Comparison of Outcomes of Total Laparoscopic Hysterectomy versus Total Abdominal Hysterectomy - Sajida Imran; Sahar Ali; Zahra Samreen (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Hysterectomy is the most common gynecological procedure performed worldwide. Recently, total laparoscopic hysterectomy (TLH) has been presented as an effective substitute for total abdominal hysterectomy (TAH). Objective: To compare operative and postoperative outcomes of TLH with TAH. Methods: This Quasi-experimental study was conducted at the department of Obstetrics and Gynecology of Hameed Latif hospital, Pakistan from December 2018 to June 2019. A total of 116 patients (58 in each group) undergoing hysterectomy, meeting the selection criteria were included in the study. Intraoperative and postoperative evaluations included intraoperative blood loss estimation and post-operative hospital stay. All data were recorded in a predesigned study proforma. Data were analyzed through SPSS version 23. Results: The mean age of patients in TLH and TAH was 47.28±4.62 years and 47.22±4.72 years respectively. The mean blood loss in the TLH group was 216.28±149.85 ml and in TAH group was 371.38±147.16 ml with statistically significant lower mean blood loss in TLH group (p-value < 0.001). Mean duration of hospital stay in the TLH group was 2.28±1.23 days and in the TAH group versus 3.86±1.30 days in TAH group (p-value < 0.001). Conclusion: Mean blood loss and hospital stay were statistically lower in TLH when compared with TAH. Adequate training of the staff can ensure adoption of laparoscopic procedure due to improved intraoperative and postoperative outcomes.